Teachers' conceptions on environment and GMO in twelve europen countries - Clément, Pierre (2010)
We analyze the conceptions of 4248 teachers on Environment and GMO (Genetically Modified Organisms), in 12 European countries: Cyprus, Estonia, Finland, France, Germany, Hungary, Italy, Lithuania, Malta, Poland, Portugal, Romania. Most of the differences between teachers' conceptions are observed inside each country. Some of them (related to preservation or utilization of Environment) significantly differentiate the 12 countries. Biology teachers have more knowledge on GMO and more opinions pro- GMO than their colleagues. Female teachers are significantly more anti-GMO than their male colleagues. More a teacher studied at University, more he or she thinks that the resources of our planet are limited.